2017
DOI: 10.1089/neu.2016.4608
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Inhibits Neuronal Apoptosis in Spinal Cord Injury through Down-Regulation of Cdc42-MLK3-MKK7-JNK3 Axis

Abstract: The mechanism by which spinal cord injury (SCI) induces neuronal death has not been thoroughly understood. Investigation on the molecular signal pathways involved in SCI-mediated neuronal apoptosis is important for development of new therapeutics for SCI. In the current study, we explore the role of heme oxygenase-1 (HO-1) in the modulation of mixed lineage kinase 3/mitogen-activated protein kinase kinase/cJUN N-terminal kinase 3 (MLK3/MKK7/JNK3) signaling, which is a pro-apoptotic pathway, after SCI. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…Heme oxygenase (HO) is a highly conserved enzyme involved in the secondary injury process, it degrades heme into biliverdin, carbon monoxide, and free iron (Fe 3+ ). Genetic or pharmacological upregulation of HO-1 activity preserves spinal cord function and restrains the neuron death after SCI [ [8] , [9] , [10] , [11] , [12] , [13] ]. As a heme degradation product, carbon monoxide (CO) has been proved to have various bioactivity such as anti-inflammatory, anti-apoptotic and antioxidant in low concentration [ [14] , [15] , [16] ], which might explains the HO-1-induced protection following SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Heme oxygenase (HO) is a highly conserved enzyme involved in the secondary injury process, it degrades heme into biliverdin, carbon monoxide, and free iron (Fe 3+ ). Genetic or pharmacological upregulation of HO-1 activity preserves spinal cord function and restrains the neuron death after SCI [ [8] , [9] , [10] , [11] , [12] , [13] ]. As a heme degradation product, carbon monoxide (CO) has been proved to have various bioactivity such as anti-inflammatory, anti-apoptotic and antioxidant in low concentration [ [14] , [15] , [16] ], which might explains the HO-1-induced protection following SCI.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, JNK3 has been implicated in several neurodegenerative diseases, both acute and chronic. JNK3 activation has a key role in triggering apoptosis [ 91 ] and neuronal death in several neurodegenerative disorders [ 92 , 93 ]. In addition, recently it has been shown that JNK3 regulates “synaptopathy” [ 94 , 95 , 96 ], which is the first degenerative event of the excitatory synapses that leads to a phase of “spine dysfunction/injury” common to many brain diseases.…”
Section: Jnk3 In the Central Nervous Systemmentioning
confidence: 99%
“…Normal cellular functions are controlled by cells by maintaining the oxidant and antioxidant balance. In response to oxidative stress, Nrf2 induces not only the expression of a number of antioxidant genes but also the activity of various antioxidant enzymes, such as HO-1, SOD, and GPx (Wang et al, 2012;Lin et al, 2017;Wei et al, 2018). As an indicator and regulator of oxidative stress, the Nrf2/HO-1 signaling pathway has been demonstrated to play a substantial role in protecting against oxidative stress for many years (Gan and Johnson, 2014;Freitas et al, 2015;Lu et al, 2018;Wei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Heme oxygenase-1 (HO-1) is known as an endogenous antioxidative enzyme in the injured spinal cord. Several studies have shown that HO-1 is sustained in traumatic SCI (Lin et al, 2016(Lin et al, , 2017Lee et al, 2017). Furthermore, HO-1 was found to stabilize the blood-spinal cord barrier and limit oxidative stress and white matter damage in the acutely injured murine spinal cord (Lin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%